AN EVALUATION ON THE DIALECTS OF HATAY AND SIIRT REGARDING THE QURANIC ARABIC - Abdulmuttalip ARPA (Fırat University, 2019)
If a language is spread among large masses and talked by many people, it is impossible that this language keeps its original aspects. Sooner or later, the differences that the language adopts create dialects. Arabic, as in the case of other languages, had to obey to this rule and gave birth to several dialects in a large geographic region. A dialect’s value is closely linked to its usage as a piece of evidence, its strength or weakness and to its closeness to the Quranic language. One of the elements, that standardized Arabic and gave it its main dimensions, is the first period Quranic language structure. Nowadays, many Arabic dialects exist all around the wold. Some of the dialects in question are mainly talked in Turkey, in the region neighbour to the Arabic geography. The dialects of Hatay and Siirt have an important place among those dialects. The aim of this study is to make some comparative identifications on how much those two populations comprehend Arabic through the dialects in question. The purpose is to state, for the dialects of Hatay and Siirt, the level of comprehension and that of sufficieny and also to put forward the distance in between those two dialects. In the research, participants from different age and socio-economic background groups will be chosen. Semi-structured model of qualitative research will be adopted. Therefore, the results will be limited to the results of the field research in question.